Reinterpretasi Pengamalan Hadis Melalui Pendekatan Linguistik Bahasa Arab - Lenni Suriyanti; Erwin Hafid; Abustani Ilyas; Amiruddin (CV. SINAR HOWUHOWU, 2026)
Hadis sebagai sumber ajaran Islam kedua setelah Al-Qur’an memiliki peran sentral dalam pembentukan As the second source of Islamic teachings after the Qur'an, the Hadith plays a central role in shaping the religious practices of Muslims. However, differences in the quality of the Hadith—ṣaḥīḥ, ḥasan, and ḍa‘īf—often give rise to debates regarding their practice, particularly when the text is understood literally without considering the linguistic characteristics of Arabic. This study aims to reinterpret the practice of the Hadith through an Arabic linguistic approach, emphasizing the analysis of lexical, syntactic, and stylistic (balāghah) aspects of the Hadith text. The research method used is qualitative-descriptive with a library research approach, using primary sources in the form of classical Hadith books and Arabic linguistic literature, as well as secondary sources from contemporary Hadith studies. The results show that a comprehensive linguistic understanding can clarify the meaning of the Hadith, distinguish between the true meaning and figurative language, and avoid errors in determining laws and practicing practices. The linguistic approach also makes a significant contribution to assessing the relevance of the practice of hadith, including the hadith of ḍa‘īf, to the realm of fadā’il al-a‘māl and Islamic education. Thus, reinterpreting the practice of hadith through an Arabic linguistic approach can strengthen the integration between the science of hadith and linguistics, and encourage a more contextual and moderate understanding of religious texts.